Patient Experiences with Oral Chemotherapy - Nurul Huda; Aulia Rika; Rismadefi Woferst; Joseph Kondwani Banda (Jurnal Keperawatan, 2022)
Introduction: Recently, oral chemotherapy has become a popular treatment modality in the treatment of cancer. However, cancer patients and their family members show to have limited knowledge on the use of oral chemotherapy safely. Objectives: The objective of the study was to explore the life experiences of breast cancer patients undergoing oral chemotherapy. Methods: A purposeful sample strategy of 3 survivors was used to gather data using semi-structured interviews. Collaizzi’s method was selected for data analysis. Results: Six major themes emerged that described the life of experiences of the patients including knowledge of oral chemotherapy, the participant’s feelings, side effects of oral chemotherapy, coping mechanisms, support system, and expectation to nurse. Participants noted that they received less information regarding their treatment, which limited them to providing appropriate care for themselves. Conclusions: It is important for nurses to give more attention and tailored education regarding oral chemotherapy, which will improve their knowledge and increase their adherence to chemotherapy.